Ethyl Cellulose-Based Micro/Nano Particle Drug Delivery Systems: A Comprehensive Review on Recent Developments - Alshehhi, Abrar Saif; Alyaqoubi, Reem Khaled; Suliman, Reem; Alrashdi, Hind; Muniyandy, Saravanan (Journal of Research Updates in Polymer Science, 2026)
This review evaluates the formulation performance, encapsulation efficiency, and drug-release behaviour of ethyl cellulose-based micro- and nanoparticles for drug delivery. A systematic search of the Scopus database identified 245 initial records, from which 20 studies were selected for final analysis based on strict inclusion criteria. The results indicate that ethyl cellulose-based systems achieve encapsulation efficiencies ranging from 11% to 100%. Critical variables, including polymer concentration and preparation methods such as solvent evaporation and nanoprecipitation, significantly influence particle size and release kinetics. Specifically, higher polymer concentrations typically result in larger particle sizes and more sustained drug release profiles. The review concludes that ethyl cellulose is a highly versatile polymer suitable for oral, topical, and gastro-retentive applications. Although its application is limited by low biodegradability, ethyl cellulose-based micro- and nanoparticles remain effective and promising platforms for enhancing therapeutic efficacy and achieving controlled drug delivery.